Integrative approaches utilizing oxytocin to enhance prosocial behavior: from animal and human social behavior to autistic social dysfunction - Yamasue, Hidenori; Meyer-Lindenberg, Andreas (The journal of neuroscience, 2012)
The prevalence of autism spectrum disorder (ASD) is as high as 1 in 100 individuals and is a heavy burden to society. Thus, identifying causes and treatments is imperative. Here, we briefly review the topics covered in our 2012 Society for Neuroscience Mini-Symposium entitled “Integrative Approaches Using Oxytocin to Enhance Prosocial Behavior: From Animal and Human Social Behavior to ASD's Social Dysfunction.” This work is not meant to be a comprehensive review of oxytocin and prosocial behavior. Instead, we wish to share the newest findings on the effects of oxytocin on social behavior, the brain, and the social dysfunction of ASD at the molecular, genetic, systemic, and behavior levels, in varied subjects ranging from animal models to humans suffering from autism for the purpose of promoting further study for developing the clinical use of oxytocin in treating ASD.